Effect of length and diameter of tapered posts on the retention - (:unkn) unknown (BLACKWELL PUBLISHING LTD, 2002)
The force transmission of tapered unthreaded posts along the root has been reported to be homogenous but their retentive strength was found to be lower compared with those of parallel unthreaded or other kinds of threaded posts. The purpose of this in vitro study was to investigate the effect of length and diameter on the retentive strength of sandblasted tapered prefabricated titanium posts (Erlangen post system(R)). Posts with constant taper angle but with three different lengths (9, 12, 15 mm) and apical diameters (0.5, 0.9, 1.1 mm) were cemented using zinc phosphate cement into the prepared and roughened post spaces of 90 intact anterior teeth. The post retention concerning length and diameter, being independent from each other, was measured by a tensile force test. The retentive strength was found to be proportional to the length as well as to the diameter of the posts. The mean minimum strength (181+/-14 N) recorded for the thinnest and shortest post was significantly lower than that of mean maximum strength (612+/-85 N) obtained from those of the thickest and longest post. Proportional bond strengths of the posts comprising their surface areas ranged between 6.8 and 7.9 N mm(-2) which were not significantly different between any group. The retention was effected strongly with the increase in the length (approximately 100%) than with the increase in the diameter (approximately 60%). Concerning the posts tested in this study, it is concluded that some caution should be exercised in the choice of post with appropriate length rather than diameter for the tooth concerned.
Keywords: prefabricated post; post size; retention; ENDODONTICALLY TREATED TEETH; STRESS-DISTRIBUTION; CORE SYSTEMS; RESTORATION; DESIGN; DOWELS; PHILOSOPHIES; RESISTANCE; FRACTURE; STRENGTH